A Direct Numerical Simulation analysis of pressure variation in turbulent premixed Bunsen burner flames-part 2: Surface Density Function transport statistics. (15th September 2018) - Klein, M.; Alwazzan, D.; Chakraborty, N.
Highlights: Surface Density Function transport analysed for DNS of turbulent Bunsen flames. Effects of pressure and Reynolds number variations analysed using DNS data. Effective normal strain rate remains insensitive to the pressure variation. DL instability at high pressure affects tangential strain and curvature stretch. Mean contributions of curvature stretch and tangential strain counter each other. Abstract: The effects of pressure variation on the transport statistics of the magnitude of the reaction progress gradient (i.e. Surface Density Function (SDF)) have been investigated based on three-dimensional simple chemistry Direct Numerical Simulations (DNS) of Bunsen burner flames representing the flamelet regime of combustion. The large length scale separation between the nozzle diameter and flame thickness for high pressure flames makes the Darrieus–Landau (DL) instability highly likely, which in turn affects the curvature stretch. It has been found that the effective normal strain rate remains insensitive to the pressure variation for the parameter range considered here, which makes the flamelet thickness in turbulent flames comparable to the laminar flame thickness. The influences of the DL instability on the positive mean tangential strain rate counter the effects of instability on the negative mean curvature stretch and thus the effective tangential strain rate (or net flame stretch rate) remains mostly unaffected by the pressure variation within the strict flamelet regime (i.e. wrinkled flamelets and corrugated flamelets regimes) of combustion. The similarities in the SDF and the effective strain rate statistics for different values of pressure suggest that the models for the Flame Surface Density and Scalar Dissipation Rate, which were originally proposed and validated for atmospheric combustion, might remain valid also for elevated pressures.